2002
DOI: 10.1051/animres:2002032
|View full text |Cite
|
Sign up to set email alerts
|

Does early thermal conditioning sometimes fail to improve the resistance of broilers to heat stress?

Abstract: -Early age thermal conditioning (TC) by exposing young chicks to 40o C for 24 hours reduces body temperature (Tb) and improves long-term broiler resistance to heat stress. Three experiments were performed under semi-controlled tropical environmental conditions to evaluate the factors affecting TC efficacy. The addition of infrared bulbs during TC reduced growth and increased water intake compared to gas heaters at similar ambient temperatures (Ta). TC consistently reduced the Tb of chickens at 7 and 40 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(38 reference statements)
1
2
0
1
Order By: Relevance
“…Heat exposure program (at 3-5 days of age, 4 and 8 weeks of age) might enhance thermo-tolerance of laying hens that would face severe heat stress in advanced or later ages (Yahav and McMurtry, 2001). These results agree with the results of Morsy (2013); Nagwa, Ahmed et al, 2004El-Moniary et al (2010); Zulkifli et al, 2003Zulkifli et al, & 2009De Basilio et al, 2002& 2003Faisal et al (2008);El-Badry et al (2009); Star et al (2009) and Mahmoud, Hanan (2006), they used heat shock exposure programs to acclimate birds to heat stress and enhance some physiological responses of birds.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Heat exposure program (at 3-5 days of age, 4 and 8 weeks of age) might enhance thermo-tolerance of laying hens that would face severe heat stress in advanced or later ages (Yahav and McMurtry, 2001). These results agree with the results of Morsy (2013); Nagwa, Ahmed et al, 2004El-Moniary et al (2010); Zulkifli et al, 2003Zulkifli et al, & 2009De Basilio et al, 2002& 2003Faisal et al (2008);El-Badry et al (2009); Star et al (2009) and Mahmoud, Hanan (2006), they used heat shock exposure programs to acclimate birds to heat stress and enhance some physiological responses of birds.…”
Section: Resultssupporting
confidence: 85%
“…Nowadays, heat shock exposure during earlier age (growth period) is unconventional procedure to increase thermo-tolerance and acclimate birds to heat stress which led to minimize heat-related mortality, improve productive performance and feed conversion and enhance immunity responses (Emam, 2013;Morsy, 2013;Nagwa, Ahmed et al, 2004El-Moniary et al, 2010;El-Badry et al, 2009;Star et al, 2009;Zulkifli et al, 2003Zulkifli et al, & 2009Faisal et al, 2008;Mahmoud, Hanan, 2006;Rahimi, 2005;De Basilio et al, 2002;Yalcin et al, 2001;Yahav and Plavnik, 1999;Yahav et al, 1997;Yahav and Hurwitz, 1996;Davis et al, 1991 andArjona et al, 1988). Emam (2013) reported that exposure of laying hens to heat shock program (40±1 °C for 4 h from 12:00-16:00 for 3 consecutive days) at 3 days and 8 weeks of age or at 3 days, 8 and 16 weeks of age (growth period) alleviated the negative effects of heat stress on productive performance of laying hens during egg production period.…”
Section: Introductionmentioning
confidence: 99%
“…Se ha otoño, comportamiento de clara trascendencia documentado el impacto negativo del stress calórico económica. En términos de los caracteres a la faena, sobre la tasa de crecimiento y el consumo de alimento los valores observados son los habituales en este tipo en diferentes poblaciones comerciales de aves para de aves, informados en estudios previos (32) e carne (23,24,25,26) y se han informado independientemente del genotipo, las aves criadas en modificaciones de parámetros fisiológicos (27) de primavera si bien presentaron menor peso corporal síntesis proteica y de grasa periférica subcutánea en registraron mayor proporción de pata-muslo, esas condiciones (28). depusieron menor proporción de grasa y presentaron mayor rendimiento a la faena.…”
Section: Carácterunclassified
“…If the relative humidity is out of the ideal range of 60 to 70 %, the temperature within the hall needs to be adjusted. For example, if RH is near 50 %, the temperature has to be increased to 33 ºC on the first day [8]. In all stages of growth of the chicken we have to observe and ensure that chickens perceive appropriate temperature [9].…”
Section: Introductionmentioning
confidence: 99%